Implementation of Lean Warehouse to Improve the Performance of Warehouse Activities at PT. ABC - Endang Pudji W; Ilmi, Mohammad Nachrul; Yekti Condro Winursito (The Indonesian Journal of Computer Science, 2024)
PT. ABC, a company operating in the cocoa product manufacturing industry, faces challenges related to waste during the reception of large spare parts, resulting in extended lead times for receiving goods. To address these issues, it is imperative to conduct an analysis of enhancements in the spare part receiving section within the maintenance warehouse to minimize or eradicate existing waste, thereby ensuring a shorter and more efficient process for receiving spare parts. Lean warehousing, which focuses on identifying and eliminating waste in warehouse operations or processes while reducing the time required to fulfill company requirements, serves as the guiding principle. The potential time reduction achievable by eliminating non-value-added activities is estimated at 26.56 minutes, representing a 23.8% decrease